Sweet spring is returning; Spring song - Silcher, Friedrich, 1789-1860 (Composer) (Sims Song Slide Corporation (Kirksville, Mo.), 2024)
Songs; Scores; Glass lantern slide depicting score of "Sweet Spring is Returning."